PENGENALAN DAGUSIBU OBAT BERSAMA PKK KELURAHAN/KECAMATAN KARANGREJO KABUPATEN MAGETAN - Diah Nurcahyani; Vidya Kartikaningrum; Andita Nur W; Cristina Indrasari (Jurnal Bakti untuk Negeri, 2022)
Knowledge of medicine is a must for all levels of society. DAGUSIBU is one of those attempts to increase public knowledge in using and managing drugs amidst the widespread of counterfeit drugs and drugs abuse. The purpose of this community service is to provide DAGUSIBU counseling to the community, especially PKK in the Karangrejo Sub-district, Magetan Regency. This counseling is expected to increase knowledge of the use of drugs. Participants in this counseling were given material about DAGUSIBU directly and supported by teaching aids in the form of medicine as an example of the application of DAGUSIBU in active discussion. The result achieved is the increase in this counseling participants about drugs through DAGUSIBU by 44.31% from 46.27 to 90.59 forming DAGUSIBU cadres in the community. Therefore, this counseling needs to be continued to improve cadres as quality information agents to the general public, especially in the Karangrejo Sub-district, Magetan Regency.